Rotations of teeth—a systematic review - Parthiban, Ramya; Kailasam, Vignesh; Venkatasamy, Nivetha Shree (Frontiers in Oral Health, 2024)
BackgroundRotations are frequently evaluated through various assessment methods of crowding and arch dimension, with relatively few studies discussing the extent or direction of rotations and even fewer addressing the reliability of such assessments. This systematic review aims to comprehensively analyze existing classification systems for rotated teeth and assess rotation in anterior and posterior teeth, its clinical applicability, and its impact on retention and relapse.Search methodsTwo investigators conducted a comprehensive search in six databases, namely, PubMed, Scopus, Ovid, LILACS, Web of Science, and Cochrane CENTRAL, up to 28 March 2024. No specific start date was defined to ensure the inclusion of all relevant studies from the inception of each database, maximizing the comprehensiveness of our review. The search criteria included retrospective studies and the inclusion criteria were patients who were assessed for rotation in any age group. The exclusion criteria were patients who had undergone orthodontic treatment, who had fractured restorations or crowns, or who had any other tooth anomaly.Data collection and analysisIn total, 10 studies satisfying the inclusion criteria were included and 9 provided quantitative outcomes for the rotation of various teeth, while the remaining study offered qualitative results. The risk of bias assessment was performed with the help of the Newcastle–Ottawa quality assessment tool.ResultsThe skeletal Class II and Class III groups exhibited similar average positions of the first molar. Upper molar rotation was primarily observed in dental Class II patients, with a higher mesial rotation angle of 78.6°. Only one study measured the rotation for all permanent teeth. Seven studies used the mid-palatal raphe as the reference line for measuring molar rotation. No gender differences were found. It was found that there was no statistical significance in the mean values of molar rotation for the right and left sides as well as the maxillary and mandibular arches. The incisors demonstrated the highest degree of rotation (7.4°–20.2°), while the premolars and canines exhibited a slightly lower degree of rotation (3.3°–9.2°). In contrast, the molars displayed the lowest degree of rotation (0.8°–7.4°).ConclusionAfter reviewing all the studies, it was found that there is no adequate classification system to assess the rotation of anterior teeth and mandibular teeth. A universally accepted classification of tooth rotation, including a common reference line, is needed. The existing systems for posterior teeth need to be standardized and have a clinical utility to be widely accepted.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024524654, PROSPERO (CRD42024524654).